Ανίχνευση δυναμικών σεναρίων συστήματος σε ασύρματες εφαρμογές με χρήση νευρωνικών δικτύων - Ζαφειράτος, Ευάγγελος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ηλεκτρολόγων Μηχανικών και Μηχανικών Υπολογιστών. Τομέας Τεχνολογίας Πληροφορικής και Υπολογιστών, 2015)
Artificial Neural Networks gain popularity in recent years, as modern processors evolve towards a parallel approach. Traditional, sequential, logic-based digital computing excels in many areas, but has been less successful for other types of problems. The development of artificial neural networks began approximately 60 years ago, motivated by a desire to try both to understand the brain and to emulate some of its strengths and is constantly gaining attention as modern Hardware platforms evolve and offer new promising capabilities for Neural Networks development.